2021
DOI: 10.1001/jamanetworkopen.2021.12062
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Receipt of Cancer Screening and All-Cause Mortality in Older Adults

Abstract: Key Points Question Is receipt of cancer screening independently associated with 10-year mortality after accounting for comorbidities and function in older adults? Findings In this cohort study of 5342 patients in the Health and Retirement Study, receipt of breast or prostate cancer screening was associated with a lower hazard of 10-year mortality after adjusting for all variables from a prognostic index that included age, comorbidities, and function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…While in aggregate, low-value cancer screenings may pose greater risk than benefit, testing outside established recommendations must be individualized, as algorithmic decisions may misclassify patients otherwise appropriate for screening. 60 Clinicians should engage in shared decision-making with those patients. Communication strategies, decision aides, and conceptual frameworks for these challenging conversations have been proposed, supported by the American Cancer Society and the US Preventive Services Task Force.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While in aggregate, low-value cancer screenings may pose greater risk than benefit, testing outside established recommendations must be individualized, as algorithmic decisions may misclassify patients otherwise appropriate for screening. 60 Clinicians should engage in shared decision-making with those patients. Communication strategies, decision aides, and conceptual frameworks for these challenging conversations have been proposed, supported by the American Cancer Society and the US Preventive Services Task Force.…”
Section: Discussionmentioning
confidence: 99%
“…While in aggregate, low-value cancer screenings may pose greater risk than benefit, testing outside established recommendations must be individualized, as algorithmic decisions may misclassify patients otherwise appropriate for screening . Clinicians should engage in shared decision-making with those patients.…”
Section: Discussionmentioning
confidence: 99%
“…It also emphasizes the need for providers to have candid conversations with their patients regarding life expectancy as this knowledge affects women's willingness to undergo screening. A recently published study by Schoenborn et al showed that there still clearly is an important role for screening mammography to reduce 10-year allcause mortality, even when adjusted for various health comorbidities and functional status [26].…”
Section: Discussionmentioning
confidence: 99%
“…34 An analysis of outcomes in women older than 65 years found that, even after correcting for prognostic index and potential confounders, breast cancer screening was associated with reduced all-cause mortality. 35 This screening benefit was attenuated but persisted in women with reduced cognition. The authors of this analysis suggest that current algorithms might misclassify individuals as having a low life expectancy, resulting in cessation of screening that is inappropriately premature.…”
Section: Clinical Trends In De-implementation In Low-risk Breast Cancer In Older Womenmentioning
confidence: 99%
“… 41 , 42 Compounding the sparse data on cancer risk in older patients is the scarcity of evidence on the benefits of enhanced surveillance and risk-reducing strategies. Although intensive surveillance has the potential to lead to early detection, 35 the effect on survival outcomes in older people is largely unknown. Furthermore, although there is an increased risk of developing a second breast cancer in patients with a pathogenic variant in BRCA1 or BRCA2 , contralateral risk-reducing mastectomy is unlikely to confer a survival benefit.…”
Section: Clinical Trends In De-implementation In Low-risk Breast Cancer In Older Womenmentioning
confidence: 99%